ICTs for the Development of the Cognitive and Metacognitive abilities of the students with Specific Learning Disorder in Mathematics - Chatzivasileiou, Panagiota; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
This article is a literature review that analyses the cognitive and metacognitive abilities of the students with Specific Learning Disorder in Mathematics (SLDM). It aims to present the cognitive and metacognitive deficits of these students along with the ways and methods that can improve the corresponding cognitive and metacognitive abilities and analyze the role of metacognition in mathematics education. It also aims to present ICT tools that are used worldwide in order to develop and enhance these abilities. These tools are designed for the development of either the cognitive or the metacognitive abilities of the students with SLDM and include computer based and mobile applications, serious games, educational software and robotics. The results of the study indicate that the existed ICT tools for the development of the cognitive and metacognitive abilities of the students with SLDM can have a crucial impact on the improvement of the symptoms of this Specific Learning Disorder. They can enhance the cognitive abilities of the attention, the working memory and the visuospatial ability along with the mathematical ability and also improve the metacognitive abilities such as reflection, self-regulation, the problem solving ability and the mathematical metacognition.